Neighborhood “Choice Architecture”: A New Strategy for Lower-Emissions Urban Planning? - Mehaffy, Michael W. (2018)
Recent advances in the field of behavioral economics offer intriguing insights into the ways that consumer decisions are influenced and may be influenced more deliberately to better meet community-wide and democratic goals. We demonstrate that these insights open a door to urban planners who may thereby develop strategies to alter urban-scale consumption behaviors that may significantly reduce greenhouse gas (GHG) emissions per capita. We first hypothesize that it is possible, through feasible changes in neighborhood structure, to alter the “choice architecture” of neighborhoods in order to achieve meaningful GHG reductions. We then formulate a number of elements of “choice architecture” that may be applied as tools at the neighborhood scale. We examine several neighborhoods that demonstrate variations in these elements, and from known inventories, we generate a preliminary assessment of the possible magnitude of GHG reductions that may be available. Although we acknowledge many remaining challenges, we conclude that “neighborhood choice architecture” offers a promising new strategy meriting further research and development.